THE INFLUENCE OF SOCIAL MEDIA MARKETING ON REPURCHASE INTENTION THROUGH BRAND AWARENESS AND PERCEIVED VALUE IN HAUS PRODUCT - Kaiwa, Ogan; Yuliati, Lilik Noor; Nurhayati, Popong (ASEAN Marketing Journal, 2024)
Manuscript type: Research article Research Aims: This research aims to analyze the influence of social media marketing on repurchase intention through brand awareness and perceived value of Haus products Design/methodology/approach: Data collection was carried out by distributing questionnaires online using Google Forms. This research method uses quantitative with a total of 200 respondents who are at least 17 years old, have purchased Haus products, are Instagram users, and know or have visited the Haus Instagram social media account. Sampling was carried out using the voluntary sampling method. Research Findings: The result shows that social media marketing has a positive and significant effect on brand awareness, repurchase intention and perceived value. Brand awareness has a positive and significant effect on repurchase intention. Perceived value has a positive and significant effect on repurchase intention. Social media marketing has a positive and significant effect on repurchase intention through the mediating variable of brand awareness. Also, Social media marketing has a positive and significant effect on repurchase intention through the mediating variable of perceived value. Theoretical Contribution/Originality: Provide insight regarding value that drive in repurchase intention on Haus product by using social media marketing. Practitioner/Policy Implication: Provide insight to improve Haus’s social media marketing through brand awareness and perceived value. Research limitation/Implication: This research only focuses on Instagram social media.